RECONSTRUCTION OF CHIN DEFECT POST BASAL CELL CARCINOMA EXCISION USING RHOMBOID FLAP: A CASE REPORT - Togatorop, Yeremia Maruli; Saktrio D. Subarno (Universitas Airlangga, 2025)
Highlights: BCC is strongly associated with UV radiation exposure,commonly affecting the face, but the chin is rarely involved (1.2% incidence). Chin reconstruction after BCC excision is challenging, requiring careful flap selection for function and aesthetics. The rhomboid flap is a preferred choice, offering good blood supply, minimal tension, quick healing, and better cosmetic results. Abstract: Introduction: Basal cell carcinoma (BCC) is a malignant skin tumor with the highest incidence and originates from the basal cells of the epidermis, with the nodular type being the most common. Case Illustration: A 76-year-old female patient came with complaints of a lump on the chin that had enlarged and bled easily for 3 years before entering the hospital. The patient was diagnosed with Basal Cell Carcinoma in the chin region. Discussion: Wide excision was performed under local anesthesia, then the wound was closed with a rhomboid flap. Evaluation after 1 month post-operatively the wound closed well and the scar was disguised. Conclusion: The chin is a unique aesthetic area with unique contours and shapes, making it a challenge for plastic surgeons to perform reconstruction after extensive BCC excision. The rhomboid flap is a very versatile local flap because it can be used almost anywhere on the body, including the chin.